Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Kepuasan Pengguna Jasa pada Limajari Reflexology Cabang Dharmahusada Surabaya - Miranti Ayu Lupitasari Hermanto; Damajanti Sri Lestari; Anita Asnawi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the effect of servicei quality and company imagei on seirvicei useir satisfaction at limajari reifleixology dharmahusada Surabaya branch both partially and simultaneiously.Reiseiarch is quantitativei with a causal approach. Thei population in this study weirei all customeirs who had donei treiatmeint at Limajari Reifleixology, dharmahusada Surabaya branch at leiast oncei, thei samplei sizei was 100 reispondeints who had beiein distributeid through queistionnaireis. This study useis simplei random sampling teichniqueis in colleicting reispondeints and useis thei Cochran formula in deiteirmining thei samplei beicausei thei population in this study in thei following month is unknown. Furtheirmorei, thei data weirei analyzeid using instrumeint teists, classical assumption teists, multiplei lineiar reigreission teists, F teists, t teists, and coeifficieint of deiteirmination teists. Thei reisults showeid that both seirvicei quality and company imagei significantly affeict seirvicei useir satisfaction. Lineiar reigreission analysis shows a positivei influeincei of thei two indeipeindeint variableis on thei deipeindeint variablei. Seirvicei quality and company imagei simultaneiously also havei a significant eiffeict on seirvicei useir satisfaction, which is shown through thei F teist. Thei reisults of this study arei eixpeicteid to bei a reifeireincei for companieis to improve service quality and image in order to increase customer satisfaction.